Android-Based Mobile Application for Vocabulary Learning - Hesty Puspitasari; Ruth Febry Maharani; Wawan Herry Setyawan; Yusniari Primasari (Universitas Pendidikan Ganesha, 2022)
The improvements in technology have made it inevitable to use in learning vocabulary. It is an undeniable fact that learning styles affect the use of applications. Accordingly, this study is aimed to analyze the efficacy of mobile applications based on Android for learning vocabulary to tenth-level learners. At this point, the product is a mobile application for learning vocabulary completed with teachers’ and students’ books for learning guides. The researchers apply Research and Development with 20 students and five teachers as research participants randomly from two Senior High Schools. The instruments used tests, guiding interviews, guiding Observations, and questionnaire. The process data is collected by systematically searching and arranging the interview transcript, field notes, validation expert, and other materials you accumulate to support the data found. Then the researchers analyze data using triangulation data. The results of the first step prove that problem-solving abilities are shown; students need help remembering unfamiliar and mastering the meaning of foreign words. The result of the design and Development indicates that the Mobile Application was valid. The results of the product experiment prove that this form is appropriate to be applied to students in vocabulary upgrading and is claimed to be sourced in general. At the same time, the product test result shows that the essential has an important effect on students’ vocabulary. The “Vocabulary App” media improves students' vocabulary.